Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Pada Materi Pokok Suhu Dan Kalor Kelas X T.A 2011/2012 - Febriani Hastini Nasution (Institut Pendidikan Tapanuli Selatan, 2016)
The purpose of this research was to find out the effectiveness of jigsaw cooperative learning model in heat and temperature on student’s learning outcomes grade X in Academic Year 2011/2012. The research method was quasi experimental. The population were seventy (70) students grade X semester II SMA Swasta Muhammadiyah 1 Medan and all of the population became sample of this research. The sample were divided into two classes, experimental and control class. Based on the data tabulation obtained:(1) The post-test mean value of the experimental class was 69.47 and 56.56 was the mean value for control class. (2) The mean value of instrument’s sensitivity index in experimental class was 0.276 that was in sensitivecategory while in control class was 0.187 which meant the requirement of good sensitivity index of instrument was not fulfillment. (3) The percentage result of class learning mastery in experimental class was 86.1 % that was categorized passed meanwhile in control class was 58.8 % that was categorized not passed. (4) The mean value of activities observation result in experimental class was 74.38 while in control class was 70.63 that were included in good category. Based on the obtained results can be concluded that jigsaw cooperative learning model is more effective than direct instruction learning model on student’s learning outcomes.